Determinants of Neutral Antagonism and Inverse Agonism in the β2-Adrenergic Receptor - Calderon Reyes, Jacqueline; Ibrahim, Passainte; Gobbo, Dorothea; Gervasio, Francesco Luigi; Clark, Timothy (Journal of Chemical Information and Modeling, 2024)
Free-energy profiles for the activation/deactivation of the β2-adrenergic receptor (ADRB2) with neutral antagonist and inverse agonist ligands have been determined with well-tempered multiple-walker (MW) metadynamics simulations. The inverse agonists carazolol and ICI118551 clearly favor single inactive conformational minima in both the binary and ternary ligand-receptor-G-protein complexes, in accord with the inverse-agonist activity of the ligands. The behavior of neutral antagonists is more complex, as they seem also to affect the recruitment of the G-protein. The results are analyzed in terms of the conformational states of the well-known microswitches that have been proposed as indicators of receptor activity.
CRIS-Team Scopus Importer:2024-04-05
Keywords: Agonists; Antagonists; Conformation; Ligands; Receptors